Combined optogenetics and voltage sensitive dye imaging at single cell resolution - Willadt, Silvia; Canepari, Marco; Yan, Ping; Loew, Leslie M.; Vogt, Kaspar E. (Frontiers in Cellular Neuroscience, 2014)
Information processing in the central nervous system makes use of densely woven networks of neurons with complex dendritic and axonal arborizations. Studying signaling in such a network requires precise control over the activity of specific neurons and an understanding how the synaptic signals are integrated. We established a system using a recently published red-shifted voltage sensitive dye in slices from mice expressing channelrhodopsin (Ch) in GABAergic neurons. Using a focused 473 nm laser for Ch activation and 635 nm laser wide field illumination for voltage sensitive dye excitation we were able to simultaneously measure dendritic voltage transients and stimulate inhibitory synaptic connections. The combination of these techniques provides excellent spatiotemporal control over neuron activation and high resolution information on dendritic signal processing.